Analysis Of Hpp Calculations With The Full Costing Method As A Basis For Setting The Selling Price Of Homecare Products - Miranti, Shintya; Hurriyaturrohman, Hurriyaturrohman; Rizqi, Muhammad Nur (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
This study aims to know the accurate calculation of the cost of production so that it can determine the selling price of products at PT Cheimiko Multi Lestari based on the full costing method where this calculation method includes all costs both variable and fixed, namely raw material costs (BBB), factory overhead (BOP), and direct labor costs (BTKL), this research method uses a qualitative method which focuses on research observations and leads to descriptive and uses a quantitative method which calculates the data obtained by PT Chemiko Multi Lestari into the cost accounting group. The results of this study indicate that the calculation of the cost of production at PT Cheimiko Multi Leistari yields a cost of production of IDR 43.350 for Detergent Fresh Lavender products and IDR 44.800 for Softener Fresh Lavender products (5 Liter size), thus obtaining a selling price of IDR 44.350 for Detergent Fresh Lavender products. and IDR 50.800 for the Softener Fresh Lavender product (5 Liter size) with a profit (margin) from each product of IDR 1.000 and IDR 6.000. While the calculation using the full coting method produces a production cost of IDR 25.368 for Detergent Fresh Lavender products and IDR 21.918 for Softener Fresh Lavender products, then results in a selling price of IDR 32.877 for Softener Fresh Lavender products (each size 5 Liter) from the calculation of the full costing method respectively each product has a profit of IDR 12.684 and IDR 10.959. So that the difference in the calculation of the cost of goods at PT Cheimiko Multi Lestari has a small profit and the calculation using the full costing method has a large profit for 10.000 pcs of finished product, therefore the calculation of the cost of production using the full costing method is very influential both in determining the selling price to compete between other competitors